THE USE OF R.A.P PARAPHRASING STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION AT CLASS X.A3 IN SMKN 2 SINGARAJA IN ACADEMIC YEAR 2013/2014 - ., I Gede Gangga Suwana; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini dapat dikategorikan sebagai sebuah penelitian tindakan kelas yang dilaksanakan dengan tujuan meningkatkan kemampuan membaca siswa-siswi kelas X.A3 di SMKN 2 Singaraja pada tahun ajaran 2013/2014 melalui penerapan R.A.P Paraphrasing Strategy. Terdapat dua siklus yang dilaksanakan pada penelitian ini, yang mana masing – masing terdiri dari empat aktivitias utama yakni perencanaan, tindakan, observasi, dan refleksi. Dalam proses pengumpulan data, terdapat 3 jenis instrumen yang digunakan antara lain catatan harian peneliti, kuisioner, serta materi tes. Kemudian, data yang telah diperoleh dianalisa secara kuantitatif dan kualitatif. Data pada pre-test dan post-test dianalisa secara kuantitatif, sementara data yang diperoleh dalam kuisioner dan catatan harian peneliti dianalisa secara kualitatif. Berdasarkan hasil yang diperoleh dalam penelitian ini, ditemukan bahwa kemampuan membaca siswa – siswi kelas X.A3 telah meningkat secara signifikan. Hasil pre-test menunjukkan bahwa dari 35 siswa secara keseluruhan, hanya 14.29% siswa saja yang lulus dan mampu melewati batas nilai minimal. Namun, dalam post-test I, jumlah siswa yang lulus meningkat menjadi 71.43% siswa, kemudian dalam post-test II, jumlah siswa yang sukses melampaui batas nilai minimal meningkat secara signifikan menjadi 85.71% siswa. Disamping itu, keberhasilan penelitian ini juga didasarkan pada hasil yang diperoleh melalui kusioner serta researcher’s diary yang menunjukkan respon – respon positif siswa terhadap penerapan R.A.P Paraphrasing Strategy dalam aktivitas membaca mereka.Kata Kunci : reading comprehension, R.A.P paraphrasing strategy, English subject in vocational school The study was categorized as classroom action research which was done in purpose to improve the students’ reading comprehension at class X.A3 in SMKN 2 Singaraja in academic year 2013/2014 through the implementation of R.A.P Paraphrasing strategy. The study was done in two cycles where each cycle consisted of four main activities; planning, action, observation and reflection. To collect the data, there were three kinds of instrument used namely researcher’s diary, questionnaire, and tests. Furthermore, the data obtained in this study were analyzed quantitatively and qualitatively. The data gained in pre-test and post-tests were analyzed quantitatively, while the data from researcher’s diary and questionnaire were analyzed qualitatively. Based on the results of this study, it was found that the students’ reading comprehension at class X.A3 in SMKN 2 Singaraja had improved significantly. It was indicated by the result of students’ tests on which in pre-test, from 35 students in total, there were only 14.29% students passing the school passing grade. But in post-test I, the number increased into 71.43% students, and finally in post-test II, the criteria of success had been reached as 85.71% students could successfully pass the standard passing score. In addition, the success of the study was also based from the results of the questionnaire as well as the researcher’s diary which showed the students’ positive attitudes toward the implementation of the R.A.P Paraphrasing strategy in their reading activities. keyword : reading comprehension, R.A.P paraphrasing strategy, English subject in vocational school